Does concurrent training intensity distribution matter? - Varela-Sanz, A.; Tuimil, J. L.; Abreu, L.; Boullosa, D. A. (The Journal of Strength and Conditioning Research, 2017)
Previous research has demonstrated the influence of intensity distribution on endurance training adaptations. However, no study has addressed the influence of intensity distribution on the effectiveness of concurrent training (CT). The main objective of this study was to compare the effects of 2 CT programs with different training intensity distribution and externally equated loads on physical fitness. Thirty-one sport science students volunteered and were evaluated for resting heart rate variability (HRV), countermovement jump, bench press, half squat, and maximum aerobic speed (MAS). All were randomly distributed into either a traditional-based training group (TT; n = 11; 65-75% of MAS, combined with 10-12 repetition maximum [RM]), polarized training group (PT; n = 10; 35-40% and 120% of MAS, combined with 5RM and 15RM), or control group (CG; n = 10). After 8 weeks of training (3 days/week), TT and PT exhibited similar improvements in MAS, bench press, and half squat performances. No differences were observed between TT and PT groups for perceived loads. There were no changes in HRV for any group, although TT exhibited a reduction in resting heart rate. Compared with other groups, the PT group maintained jump capacity with an increment in body mass and body mass index without changes in body fatness. In conclusion, PT induced similar improvements in physical fitness of physically active individuals when compared with TT. However, PT produced a lower interference for jumping capacity despite an increment in body mass, whereas TT induced greater bradycardia. Extended studies with different intensity distributions should be conducted to better determine the dose-response of CT in various populations.